Temporal Preparation for Speaking in Question-Answer Sequences - Magyari, Lilla; De Ruiter, Jan P.; Levinson, Stephen C. (Frontiers in Psychology, 2017)
In everyday conversations, the gap between turns of conversational partners is most frequently between 0 and 200 milliseconds. We were interested how speakers achieve such fast transitions. We designed an experiment in which participants listened to pre-recorded questions about images presented on a screen and were asked to answer these questions. We tested whether speakers already prepare their answers while they listen to questions and whether they can prepare for the time of articulation by anticipating when questions end. In the experiment, it was possible to guess the answer at the beginning of the questions in half of the experimental trials. We also manipulated whether it was possible to predict the length of the last word of the questions. The results suggest when listeners know the answer early they start speech production already during the questions. Speakers can also time when to speak by predicting the duration of turns. These temporal predictions can be based on the length of anticipated words and on the overall probability of turn durations.